People's Republic of China : Financial Sector Assessment Program- Detailed Assessment of Observance of the Insurance Core Principles. (IMF Staff Country Reports; Country Report ;, 2017)
This paper presents an assessment of the level of observance of the Insurance Core Principles (ICPs) in China. Overall, the Chinese regulatory system is assessed to have a good level of compliance with the ICPs. The regulatory framework includes, in addition to the solvency standards, extensive requirements on corporate governance, risk management and internal controls as well as on reinsurance, disclosure and conduct of business. All these requirements are applied appropriately to the significant number of large insurance groups, which together account for the bulk of premium income. However, there is scope for further development of crisis preparedness and market conduct work.